Adaptive VSG control strategy considering energy storage SOC constraints - Han, Jinglin; Feng, Xichun; Zhao, Hui; Hu, Ping; He, Chunguang (Frontiers in Energy Research, 2023)
The virtual synchronous generator (VSG) control strategy is proposed to mitigate the low inertia problem in the power system brought about by the high percentage of distributed generation connected to the grid and the application of power electronic devices. In order to maximize the effectiveness of the advantages of the flexible and adjustable parameters of VSG control, an adaptive VSG control strategy considering SOC constraint of the energy storage unit is proposed in this paper. Considering the significant loss of service life by operating the energy storage unit at its limit state, based on the rate and degree of change in system frequency, the adaptive control strategy realizes the online adaptive adjustment of the inertia factor and damping factor under different perturbation conditions by adaptively adjusting the control parameters when the system frequency oscillates. Finally, the effects of this adaptive VSG control method and conventional VSG control method are compared by simulation in PLECS. Hardware-in-the-loop (HIL) experimental platforms and semi-physical simulation experiments are constructed on RTBOX, and the feasibility and validity of this adaptive VSG control strategy are verified.